Weibull Parameters and Wind Power Assessment for Three Locations in Iraq - Ani, Ayad; Saleh, Mohammed; Hadi, Firas; Abdulwahab, Rawnak (Iraqi Journal of Science, 2023)
In this research, we built a program to assess Weibull parameters and wind power of three separate locations in Iraq: Baghdad, Basrah and Dhi-qar for two years 2009 and 2010, after collecting and setting the data available from the website "Weather Under Ground" for each of the stations Baghdad, Basrah and Dhi-qar. Weibull parameters (shape parameter and scale parameter) were estimated using maximum likelihood estimation method (MLE) and least squares method (LSM). Also, the annual wind speed frequencies were calculated noting speed most readily available through the above two years. Then, we plotted Weibull distribution function and calculate the most significant quantities represented by mean wind speed, standard deviation of the values, the highest value and the lowest value during those years.